Maintaining Trust in Newborn Screening: Compliance and Informed Consent in the Netherlands - van der Burg, Simone (The Hastings Center report, 2012)
Newborn screening consists of taking a few drops of blood from a baby's heel in the first week of life and testing it for a list of disorders. In the United States and most countries in Europe, newborn screening programs began in the 1960s and 1970s with screening for phenylketonuria (PKU), a rare metabolic disease that causes severe and irreversible mental retardation unless treated before problems arise. As knowledge about rare diseases expanded and new screening technologies were introduced—such as the tandem mass spectrometer and high-performance liquid chromatography—the same blood sample could be used to test for a whole list of disorders. In general, screening programs in most countries have tended to expand, but in different countries they have expanded in different ways. Regulation also varies. In some states, screening is mandatory, whereas in others—Wyoming and Maryland—parents are asked for their informed consent. Germany and France have adopted an explicit informed consent procedure, whereas other European countries have a more informal “opt-out” procedure that does not require signing an informed consent form. Whether newborn screening requires informed consent is an ongoing issue in bioethics. In this article, we will focus on the tension between informed consent and the problem of compliance in newborn screening. Asking for informed consent—allowing parents to opt out—is often thought to pose a threat to compliance. Building on the work of Onora O'Neill on informed consent and trust, however, as well as on work she coauthored with Neil Manson, we will argue that informed consent procedures may actually help maintain trust in newborn screening and may therefore support compliance.